Archaeological knowledge production: reading mortuary reconstructions. (February 2023) - Moen, Marianne; Price, Neil; Pedersen, Unn
Abstract: Abstract : Research on archaeological knowledge production emphasises the contingent nature of understandings of the past. In practice, however, levels of uncertainty and conjecture can easily become less than obvious in interpretations, perhaps especially visual ones. The authors interrogate multiple textual and visual accounts of a Viking-Age burial to demonstrate how selection processes—what to portray or omit—highlight the contextual nature of the knowledge claims in these images. Arguing that the circulation of reconstructions shorn of textual nuance leads to misperceptions, the authors call for transparency in the creation of these images. Rather than definitive depictions of archaeological fact, these reconstructions offer tools for archaeologists and the public to think with.